Reconciling Scalping With Islamic Principles: A Qualitative Study on Stock Trading In Malaysia - Nik Abdul Ghani, Nik Abdul Rahim; Nazri, Hanafi (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2025)
Scalping, a high-frequency trading strategy characterized by rapid buy-and-sell transactions to capture small price movements, has become increasingly common in modern stock markets. Its legitimacy under Islamic commercial jurisprudence (fiqh muʿāmalāt), however, remains debated due to potential elements of maysir (gambling), gharar (excessive uncertainty), and bayʿ al-najash (deceptive bidding). Addressing the lack of focused research on this issue within Malaysia’s Islamic capital market, this study employs a qualitative descriptive approach through document analysis of classical jurisprudential texts, contemporary academic literature, and regulatory fatwas issued by recognized Shariah authorities. Using the takyīf fiqhī method, the analysis examines the ethical and legal dimensions of scalping to determine whether it conforms to Shariah principles. The findings reveal that although scalping carries speculative elements, it may be considered conditionally permissible (mubāḥ) when conducted transparently, guided by informed analysis, and devoid of manipulative intent. The study concludes that scalping is not inherently prohibited in Islam but requires ethical discipline and regulatory oversight to prevent exploitation. The research contributes to refining Shariah-compliant trading practices, offering practical implications for Muslim investors, Shariah scholars, and regulators in strengthening ethical governance within Malaysia’s dynamic Islamic financial system.